Hamburg als Standort der privaten Universal-/Großbanken im 19. und frühen 20. Jahrhundert - Detlef Krause (IBF - Institut für Bank- und Finanzgeschichte, 2017)
Hamburg as a Site of Private Full-service/ Major Banks in the 19th and Early 20th Centuries: The Hamburg banking sector experienced considerable structural changes in the period from 1850 until into the 1930s. Around 1856 and 1870, a large number of new banks were founded, mostly in the form of stock corporations. Starting in the 1890s, the banking center saw a consolidation with foreign banks locating there and the commencement of foundings of branches. What is striking is the bilateral integration of Hamburg with Berlin, the financial center. While the banking relationships with the imperial capital meant a relative loss of importance for the local Hamburg banks, it also brought a considerable overall benefit to Hamburg as a financial center. Typical for the Hamburg financial center was the major and long-standing significance of the merchant banker, whose business was rooted primarily in the mercantile trade. Also striking was the large number of small private banking businesses in the 1920s.
Keywords: G21; N23; N24; 330